Gambaran Jumlah Leukosit Pada Penderita Suspek So TB Paru di Rumah Sakit Patuh Patut Patju - Reginata, Ni Luh Vira; Rohmi, Rohmi; Manu, Thomas Tandi; Khusuma, Ari (Jurnal Laboratorium Khatulistiwa, 2024)
Leukocyte examination is carried out to describe disease events or processes in the body, aspecially infectious diseases such as tuberculosis bacteria can attack immune system cells, including leukocytes. Bacteria can survive and reproduce in leukocytes. Pulmonary TB sufferers before treatment saw an increases in leukocyte levels, indicating the formation of many leukocytes to fight bacteria in the phatocytosis process. On of the laboratory tests used to support the diagnosis of tuberculosis is an examination of the leukocyte count. This study aimed to determine the description of the number of leukocytes in patients with Suspected SO Pulmonary TB at The Patuh Patut Patju Hospital Untuk. This study design is descriptive case study research. Sampling technique was carried out using accidental sampling technique and  30 respondents obtained. The results of this study showed that the average leukocyte levels of patients with suspected SO Pulmonary TB were 9,643/μl, with 13 people (1+), 12 people (2+), 5 people (3+). The highest average leukocyte count was found in the female gender, age group 56-65 years and on 5 months treatment